Marandu palisade grass-forage peanut mixed pastures: Forage intake, animal behaviour, and canopy structure as affected by grazing intensities - Rodrigues da Cruz P.J. (2024)
© 2024 John Wiley & Sons Ltd.Integrating forage legumes into grasslands offers numerous ecosystem services. However, the management of grass-legume pastures is challenging because the interaction between the defoliation frequency and severity may affect the legume persistence and forage intake by grazing animals. This 2-year study evaluated the most effective grazing intensity to increase forage intake while maintaining a balanced legume proportion in tropical pastures consisting of Brachiaria brizantha and Arachis pintoi. Three treatments (grazing intensities) were assessed: severe, moderate, and low, corresponding to stubble heights of 10, 15, and 20 cm, respectively, and a pre-grazing height of 25 cm. Two purebred Tabapua heifers were used for each treatment, and additional put-and-take animals were introduced, as required. Canopy structure, grazing behaviour, nutritive value, and forage intake were evaluated. The legume proportion in herbage mass remained consistent across all intensities, averaging 35% pre- and 32% post-grazing. The grazing duration remained consistent across treatments on the first and third days, with an average grazing time of 390 and 440 min, respectively. Under post-grazing conditions, low-intensity grazing had a 52% greater intake rate than severe-intensity grazing, which was attributed to a greater biting rate (37.9 bites/min) and bite weight (0.9 g DM/bite). Moderate grazing intensity (stubble height of ~15 cm associated with a pre-grazing height of ~25 cm) is recommended to manage a mixture of B. brizantha and A. pintoi when the objective is to couple high forage intake with a balanced legume proportion in the pasture.